Epidemiology of vector-borne diseases in cattle from SE Uganda. - McOdimba, F.A. (University of Edinburgh, 2006)
Institutions involved in vector-borne diseases research, epidemiological studies as well as vaccine development require reliable and sensitive assays to support the development of vaccine products and new drugs for treatment. These diagnostic assays also aid in identifying disease control target populations, and to monitor infection during trials for assessing the efficacy of preventive or curative drug. Molecular techniques such as the polymerase chain reaction (PCR) amplification have been used in detecting parasites of several species, sub-species and types and are favoured over microscopic examination of blood or the immunological methods because of their superior sensitivity and higher throughput. Two of the most commonly used diagnostic methods, microscopy and molecular techniques for pathogen detection and species characterization, were evaluated for their sensitivity and specificity and subsequently used in screening cattle for parasites in the blood of cattle kept under traditional mixed farming management system. Molecular methods revealed higher VBD prevalence in the cattle from the villages of Tororo and Busia districts of SE Uganda. The prevalence of trypanosome species pathogenic to livestock was found to be higher than previously documented in this area. Based on the data obtained by PCR amplification the effect of prophylactic drug intervention against trypanosomiasis was assessed over a period of six months. While isometamidium chloride treatment of cattle appeared to control trypanosomiasis in areas with low prevalence, the drug had no effect in controlling the disease in high prevalence areas. It would therefore be necessary to combine the use of drug intervention with other methods such as vector control, to reduce the prevalence, in order to realize effective control of trypanosomiasis.